PELATIHAN SISTEM DAN PROSEDUR SIMPAN PINJAM (BUMDes) (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
To run a system and procedure for savings and loans on BUMDes, a system is needed that can help in the flow of savings and loans in the form of a flowchart system, and for this procedure provides guidance in managing the complete administration of customer data in the form and slip. So that the administrator can find out whether a program is feasible or not feasible to run. Financial aspects are aspects that are used to assess the company's finances as a whole. This aspect is just as important as other aspects, there are even some entrepreneurs who consider this aspect to be the most important to be analyzed because from this aspect it is clearly illustrated the matters relating to company profits, so that it is one of the very important aspects to be examined for its feasibility. Banking is always connected financially, and here it is clear that the savings and loan program is always related to finance. With the flowchat, forms, and financial reporting, of course, it will make it easier to run this program, diflowchat above explains the paths from registration to reporting, the forms above are very clear that customers who will conduct transactions can directly fill out forms that already provided and for reporting, namely for archives held by BUMDes or BUMDes management, so it can be directly used or executed.